Youth diet quality and hazard of mood disorder in adolescence and adulthood among an Australian cohort - Wilson, JE; Blizzard, L; Gall, SL; Magnussen, CG; Oddy, WH; Dwyer, T; Venn, AJ; Smith, KJ (Elsevier, 2020)
Background Prospective studies on youth diet and mood disorders outcomes are limited. We examined if youth diet quality was associated with mood disorder onset over a 25-year follow-up period.